Correção da acidez no perfil do solo para implantação de culturas anuais - Silva, Junior Cézar Resende (2021)
In the last 10 years, around 1.5 million hectares of new areas have been incorporated into grain production systems in Brazil each year. Most of these areas show some form of soil degradation, mainly related to low nutrient content and high acidity. Thus, the transformation of these areas into high productivity environments initially involves correction of soil acidity and adequacy of Ca and Mg contents. However, there are still questions about the methodologies used for limestone recommendation in Brazil, as in many situations the doses recommended by official methodologies have not been sufficient for adequate soil correction, leading technicians and producers to use corrective doses far above the recommended, based on local experience but not proven by research. Therefore, the objective of this study was to evaluate the efficiency of increasing doses of limestone in correcting soil acidity, availability of basic cations and productivity of soybean and sorghum crops. The work was carried out in two experimental areas located in the Triangulo Mineiro region, under a sandy-loamy Red Latosol and a clayey Red Latosol. The experimental design used was a randomized block design, with four replications. The treatments consisted of six doses of limestone (0, 4, 8, 12, 16 and 20 Mg ha-1), incorporated with a 32-inch grid, with the objective of reaching a layer of 0,0-0,40 m of depth. Another experiment was carried out in a greenhouse, incubating for 90 days, proportionally, the same doses used in the field, mixed with a volume of 2 dm-3 of soil collected from the 0,0-0,40 m layer. The results were submitted to analysis of variance and when there was a difference between limestone doses, the regression analysis was tested. In general, it was possible to observe that liming promoted an increase in pH and V% values and in Ca and Mg contents, and also reduced H+Al contents in field and incubation experiments. The concentrations of Cu, Fe, Mn, Zn and Fe in soybean leaves reduced with the use of the highest doses of limestone, remaining generally close to or above the critical level. Yields increased, reaching the maximum yield with doses close to 6.5 Mg ha-1 and 20 Mg ha-1 in Site1, with sandy loam soil and in Site2, with clayey soil, respectively.